The role of neurotrophine‐3 in traumatic brain injury. Issue 2 (28th June 2018) - Chao‐Zhang,; Zhu, Yu‐Hang
Abstract : Traumatic brain injury (TBI) is the most common cause of long‐term disability worldwide. It is devastating and usually causes moderate or severe injuries, which includes a period of decreased responsiveness, especially leading to neurological function deficits. Although some effective treatment methods are available, it is far from effective, also adequate drug treatment for TBI and its mechanism still remains unclear. Meanwhile, a large number of researches have proved that neurotrophin‐3 (NT‐3) plays an important role in nervous system, but the concrete role of NT‐3 in TBI is also needing to be recognized. So, the goal of this review is to summarize the role of NT‐3 so as to provide a potential explaination and effective treatment for TBI in future clinic practice.